Endoscopic ultrasound‐guided gallbladder drainage as a first approach for jaundice palliation in unresectable malignant distal biliary obstruction: Prospective study - Mangiavillano, Benedetto; Moon, Jong Ho; Facciorusso, Antonio; Vargas‐Madrigal, Jorge; Di Matteo, Francesco; Rizzatti, Gianenrico; De Luca, Luca; Forti, Edoardo; Mutignani, Massimiliano; Al‐Lehibi, Abed; Paduano, Danilo; Bulajic, Milutin; et al. (Digestive endoscopy, 2024)
Objectives Endoscopic retrograde cholangiopancreatography (ERCP) represents the gold standard for jaundice palliation in patients with distal malignant biliary obstruction (DMBO). Biliary drainage using electrocautery lumen apposing metal stent (EC‐LAMS) is currently a well‐established procedure when ERCP fails. In a palliative setting the endoscopic ultrasound‐guided gallbladder drainage (EUS‐GBD) could represent an easy and valid option. We performed a prospective study with a new EC‐LAMS with the primary aim to assess the clinical success rate of EUS‐GBD as a first‐line approach to the palliation of DMBO. Methods In all, 37 consecutive patients undergoing EUS‐GBD with a new EC‐LAMS were prospectively enrolled. Clinical success was defined as bilirubin level decrease >15% within 24 h and >50% within 14 days after EC‐LAMS placement. Results The mean age was 73.5 ± 10.8 years; there were 17 male patients (45.9%). EC‐LAMS placement was technically feasible in all patients (100%) and the clinical success rate was 100%. Four patients (10.8%) experienced adverse events, one bleeding, one food impaction, and two cystic duct obstructions because of disease progression. No stent‐related deaths were observed. The mean hospitalization was 7.7 ± 3.4 days. Median overall survival was 4 months (95% confidence interval 1–8). Conclusion Endoscopic ultrasound‐guided gallbladder drainage with the new EC‐LAMS is a valid option in palliative endoscopic biliary drainage as a first‐step approach in low survival patients with malignant jaundice unfit for surgery. A smaller diameter EC‐LAMS should be preferred, particularly if the drainage is performed through the stomach, to avoid potential food impaction, which could result in stent dysfunction.